Ultrasonic Assisted Synthesis of Chromenes Catalyzed by Sodium Carbonate in Aqueous Media - Sabbaghan, Maryam; Sofalgar, Pegah (Combinatorial Chemistry & High Throughput Screening, 2015)
A simple, efficient, and environmentally benign procedure for the synthesis of 2-amino-4Hchromene ring has been achieved by the three-component reaction of an aromatic aldehyde, malononitrile and diverse enolizable C-H activated compound under ultrasound irradiation using sodium carbonate as a catalyst in aqueous media. Sodium carbonate as a natural salt, being available as an inexpensive catalyst combined with ultrasound method promoted this protocol in comparison to other methods and catalysts.
Keywords: sodium carbonate